Inhibition of AMD-Like Pathology With a Neurotrophic Compound in Aged Rats and 3xTg-AD Mice - Liu, Yinghua; Wei, Wei; Baazaoui, Narjes; Liu, Fei; Iqbal, Khalid (Frontiers in Aging Neuroscience, 2019)
Age-associated macular degeneration (AMD), which leads to loss of vision at its end stage, is one of most common neurodegenerative diseases among the elderly. However, to date, no effective drug therapy is available for prevention of AMD. Here we report the occurrence of AMD pathology and its prevention by chronic treatment with the neurotrophic peptidergic compound P021, in aged rats and 3xTg-AD mice. We found photoreceptor degeneration, lipofuscin granules, vacuoles, and atrophy in retinal pigment epithelium (RPE), Bruch’s membrane (BM) thickening; in aged rats, we even found rosette-like structure formation. Microgliosis and astrogliosis were observed in different retinal layers. In addition, we also found that total tau, phosphorylated tau, A/APP, and VEGF were widely distributed in the sub-retina of aged rats and 3xTg mice. Importantly, chronic treatment with P021 for 3 months in rats and for 18 months in 3xTg mice ameliorated the pathological changes above. These findings indicate the therapeutic potential of P021 for prevention and treatment of AMD and retinal changes associated with aging and Alzheimer’s disease.